2021
DOI: 10.1039/d1ra00890k
|View full text |Cite
|
Sign up to set email alerts
|

High-performance broadband photodetectors based on all-inorganic perovskite CsPb(Br/I)3 nanocrystal/CdS-microwire heterostructures

Abstract: The high performance photodetector based on CsPb(Br/I)3-NC/CdS-MW heterostructures showed broadband photodetection that covers UV-VIS-NIR range due to the charge transfer at the heterojunction interface and the absorption capability of CsPb(Br/I)3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Besides CQDs, some other semiconductor materials are also utilized to form perovskite-based heterojunctions. 21 , 40 , 81 , 82 , 83 , 84 , 85 , 86 For the perovskite/ polymer heterostructures, the addition of a variety of polymers into the perovskite materials could improve photoluminescence quantum yield (PLQY) values of resultant composites or heterostructures by passivating the surface of perovskite, by forming individually dispersed NC cores within an encapsulating polymer matrix. Such a strategy of forming heterostructures leads to a significant enhancement in PLQY due to the spatial separation of the perovskite NCs and hence the deactivation of energy transfer to dark crystals.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Besides CQDs, some other semiconductor materials are also utilized to form perovskite-based heterojunctions. 21 , 40 , 81 , 82 , 83 , 84 , 85 , 86 For the perovskite/ polymer heterostructures, the addition of a variety of polymers into the perovskite materials could improve photoluminescence quantum yield (PLQY) values of resultant composites or heterostructures by passivating the surface of perovskite, by forming individually dispersed NC cores within an encapsulating polymer matrix. Such a strategy of forming heterostructures leads to a significant enhancement in PLQY due to the spatial separation of the perovskite NCs and hence the deactivation of energy transfer to dark crystals.…”
Section: Photophysical Propertiesmentioning
confidence: 99%
“…Hu et al fabricated a germanium/perovskite heterojunction PD and obtained R values of 395, 228, and 32 A/W, and D * values of 2.8 × 10 10 , 1.6 × 10 10 , and 2.2 × 10 9 Jones at 405, 680, and 980 nm, respectively . Li et al reported a broadband (365 to 810 nm) PD based on a CsPb­(Br/I) 3 nanocrystal/CdS-microwire heterostructure, showing an R of 14.07 A/W, an EQE of 4789%, and a D * of 8.81 × 10 10 Jones at 365 nm . Hong et al fabricated a broadband self-powered PD having CuO/Si nanowires as the light absorber .…”
Section: Introductionmentioning
confidence: 99%
“…15 Li et al reported a broadband (365 to 810 nm) PD based on a CsPb(Br/ I) 3 nanocrystal/CdS-microwire heterostructure, showing an R of 14.07 A/W, an EQE of 4789%, and a D* of 8.81 × 10 10 Jones at 365 nm. 16 Hong et al fabricated a broadband self-powered PD having CuO/Si nanowires as the light absorber. 17 Recently, multi-cation (≥4) compounds have attracted great attention due to their unique physical and chemical properties.…”
Section: ■ Introductionmentioning
confidence: 99%
“…have fabricated a photodetector based on CdS/ZnS heterostructures with a very high specific detectivity of 2.23×10 14 Jones and a relatively fast response speed of 5 ms [9] . High‐performance broadband photodetector fabricated with CsPb(Br/I) 3 nanocrystals/CdS‐microwire heterostructures have shown superior photosensitivity due to the light absorption capability of perovskites and charge transfer efficiency at heterojunction interface [10] …”
Section: Introductionmentioning
confidence: 99%